2001
DOI: 10.1002/path.834
|View full text |Cite
|
Sign up to set email alerts
|

Differences in susceptibility to colonic stem cell somatic mutation in three strains of mice

Abstract: Different species and different strains of animals commonly show very different sensitivities to carcinogenic regimes, which are often unexplained. A major possible contributory factor is variation in susceptibility to mutation, but this has not been directly demonstrated. This study therefore quantified the colonic stem cell mutation frequency in three strains of mice using two carcinogens. Stem cell mutations were identified using loss of function of glucose 6-phosphate dehydrogenase (G6PD) in individual cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…The C57BL/6J mice used in our study have an intermediate susceptibility to develop colon tumors and do not typically develop other treatment related malignancies. 20,21 In one study, 48% of the C57BL/6J mice treated with DMH developed colorectal tumors. This is similar to our study in which 60% of Cables +/+ mice treated with DMH developed colorectal tumors.…”
Section: Resultsmentioning
confidence: 99%
“…The C57BL/6J mice used in our study have an intermediate susceptibility to develop colon tumors and do not typically develop other treatment related malignancies. 20,21 In one study, 48% of the C57BL/6J mice treated with DMH developed colorectal tumors. This is similar to our study in which 60% of Cables +/+ mice treated with DMH developed colorectal tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Turnover of the epithelial cells in the gastrointestinal tract is a constant process and increases after injury. Studies have shown that all gastrointestinal epithelial cell lineages come from one single stem cell 17,18 . Through asymmetric division, these cells can produce an identical daughter cell.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by observing crypts deficient in glucose-6-phosphate dehydrogenase because of gene mutation, Griffith et al have found that all the cells of a crypt derive from a single stem cell through monoclonal cell proliferation (43,44). Since all the cells in the gastrointestinal epithelium, particularly in the small intestine, are renewed in a very short time, 3-5 days, it is thought that precursor cells, not stem cells, in the proliferative zone produce a large number of mature cells in a short time.…”
Section: Discussionmentioning
confidence: 99%